Field level interventions on subclinical mastitis and detection of Staphylococcus in crossbred dairy cows - KARABASANAVAR, N S; RADDER, S K; SIVARAMAN, G K (The Indian Journal of Animal Sciences, 2019)
Mastitis has emerged as one of the major managemental diseases of economic importance of high yielding dairy cows. A cross sectional study was carried out on 116 cross-bred dairy cows of small scale dairy farms; subclinical mastitis (SCM) was detected in 22 animals (cow-wise prevalence, 18.96%). Of the 88 individual quarterâ€™s milk tested using California mastitis test (CMT) and somatic cell count (SCC) tests, 51 quarters showed SCM (quarterwise prevalence, 57.9%). Quarter-wise prevalence of SCM was 29.4, 31.4, 23.5 and 15.7% in right-fore (RF), right-hind (RH), left-fore (LF) and left-hind (LH) quarters, respectively. Fore-(52.9%) and right-(60.8%) quarters showed higher prevalence of SCM than hind-(47.1%) and left-(39.2%) quarters. All 4 quarters were found affected with SCM in 47% cows followed by 3-(23.5%), 1-(17.6%) and 2-(11.8%) quarters. Staphylococci were isolated and confirmed using 16S rRNA gene based genus-specific PCR in 39.2% of SCM affected quarters. Virulence associated nuc gene was detected in 75% of Staphylococcus isolates indicating their potential pathogenicity. Antibiogram showed multiple drug resistance (â‰¥3 antimicrobial category) in 63.6% of Staphylococci. Multiple antimicrobial resistance (MAR) was recorded in 31.8% isolates. However, none of the isolate carried mecA gene. Interventions, viz. clean milk production practices, antimicrobial therapy and non-specific supportive treatments resulted in 77.7, 50 and 38.8% reductions in SCM compared to the untreated control (37.5%). This study accentuated higher prevalence of SCM among dairy cattle and predominance of Staphylococcus as the major mastitogen. Early detection and management of SCM among dairy cattle is recommended so as to prevent its progression to clinical illness and curtail potential economic loss to farmers.